The Translocated Body: The Emergence of YASF in Colonial Bengal. Issue 2 (1st July 2022) - Bhattacharya, Atanu; Hiradhar, Preet
Abstract : Young Adult Science Fiction (YASF) assumes added significance in nineteenth-century Bengal, being located within a network of contesting discourses. During its long history, Bangla YASF negotiated a complex set of knowledge systems that frequently focused on the body of the youth. We attempt to understand this discursive space with the help of three paradigms—"technological wonder, " "pedagogic systems, " and "the medicalized body." We contend that these paradigms were instrumental in voicing subaltern concerns against the regime of British dominance. We examine Jagadananda Roy's Travel to Venus (1895), one of the earliest works of YASF written during the period, in the context of these paradigms.